Circadian rhythm of urinary potassium excretion during treatment with an angiotensin receptor blocker. (December 2014) - Ogiyama, Yoshiaki; Miura, Toshiyuki; Watanabe, Shuichi; Fuwa, Daisuke; Tomonari, Tatsuya; Ota, Keisuke; Kato, Yoko; Ichikawa, Tadashi; Shirasawa, Yuichi; Ito, Akinori; Yoshida, Atsuhiro; Fukuda, Michio; et al.
Introduction: We have reported that the circadian rhythm of urinary potassium excretion (UK V) is determined by the rhythm of urinary sodium excretion (UNa V) in patients with chronic kidney disease (CKD). We also reported that treatment with an angiotensin receptor blocker (ARB) increased the UNa V during the daytime, and restored the non-dipper blood pressure (BP) rhythm into a dipper pattern. However, the circadian rhythm of UK V during ARB treatment has not been reported. Materials and methods: Circadian rhythms of UNa V and UK V were examined in 44 patients with CKD undergoing treatment with ARB. Results: Whole-day UNa V was not altered by ARB whereas whole-day UK V decreased. Even during the ARB treatment, the significant relationship persisted between the night/day ratios of UNa V and UK V ( r =0.56, p <0.0001). Whole-day UK V/UNa V ratio ( p =0.0007) and trans-tubular potassium concentration gradient ( p =0.002) were attenuated but their night/day ratios remained unchanged. The change in the night/day UK V ratio correlated directly with the change in night/day UNa V ratio ( F =20.4) rather than with the changes in aldosterone, BP or creatinine clearance. Conclusions: The circadian rhythm of UK V was determined by the rhythm of UNa V even during ARB treatment. Changes in the circadian UK V rhythm were not determined by aldosterone but by UNa V.